Coordinated energy storage and network expansion planning considering the trustworthiness of demand-side response - Feng, Peiyun; Chen, Chong; Wang, Lin (Frontiers in Energy Research, 2024)
The enhancement of economic sustainability and the reduction of greenhouse gas (GHG) emissions are becoming more relevant in power system planning. Thus, renewable energy sources (RESs) have been widely used as clean energy for their lower generation costs and environmentally friendly characteristics. However, the strong random uncertainties from both demand and generation sides make planning an economic, reliable, and ecological power system more complicated. Thus, this paper considers a variety of resources and technologies and presents a coordinated planning model including energy storage systems (ESSs) and grid network expansion considering the trustworthiness of demand-side response (DR). Firstly, the size of one single ESS was considered as its size has a close effect on maintenance costs and ultimately affects the total operating cost of this system.Secondly, it evaluates the influence of the trustworthiness of DR. Thirdly, multiple resources, and technologies were included in this high-penetration renewable energy integrated power system such as ESSs, networks, DR technology, and GHG reduction technology. Finally, this model optimizes the decision variables such as the single size and location of ESSs, and the operation parameters such as thermal generation costs, loss load costs, renewable energy cu rtailment costs, and GHG emission costs. Since the problem scale is very large due to not only various devices but also both binary and continuous variables considered simultaneously, we reformulate this model by decomposition. Then transform it into a master problem (MP) and a dual subproblem (SP). Finally, the proposed method is applied to a modified IEEE 24-bus test system. Results show computational effectiveness and provide a helpful method in planning low-carbon electricity power systems.